1991
DOI: 10.1083/jcb.112.4.653
|View full text |Cite
|
Sign up to set email alerts
|

Beta actin and its mRNA are localized at the plasma membrane and the regions of moving cytoplasm during the cellular response to injury.

Abstract: Abstract. Previous work in our laboratory has shown that microvascular pericytes sort muscle and nonmuscle actin isoforms into discrete cytoplasmic domains (Herman, I. M., and P. A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
171
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(187 citation statements)
references
References 62 publications
(67 reference statements)
15
171
1
Order By: Relevance
“…Therefore, the double probing identified four spots that corresponded to the additive signals for both ,B-and y-actin isoforms. Furthermore, the doubly probed immunoblots confirmed that the y-actin iso- forms had more basic pl values than the ,B-actin isoforms, consistent with reports by several groups (Otey et al, 1986;Hoock et al, 1991). Our specific pl values are less than 0.1 pH unit more acidic than the corresponding values reported by Leavitt et al (1980), but this small difference might be due to the use of different standards.…”
Section: Characterization Of Gastric Actin Isoformssupporting
confidence: 58%
See 3 more Smart Citations
“…Therefore, the double probing identified four spots that corresponded to the additive signals for both ,B-and y-actin isoforms. Furthermore, the doubly probed immunoblots confirmed that the y-actin iso- forms had more basic pl values than the ,B-actin isoforms, consistent with reports by several groups (Otey et al, 1986;Hoock et al, 1991). Our specific pl values are less than 0.1 pH unit more acidic than the corresponding values reported by Leavitt et al (1980), but this small difference might be due to the use of different standards.…”
Section: Characterization Of Gastric Actin Isoformssupporting
confidence: 58%
“…Although there have been speculations on differential functions and/or subcellular localizations (Pardo et al, 1983), differences in isoform distribution and function have been minimally explored. A differential distribution of actin isoforms has been suggested based on observed enrichment of f-actin at the cell periphery (DeNofrio et al, 1989;Hoock et al, 1991). The mRNA encoding ,B-and y-actin isoforms were found to be differentially distributed in myoblasts (Hill and Gunning, 1993), whereas these same authors did not detect a spatial separation of the expressed protein isotypes.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The fact that bCYA and gCYA are differentially localized within a cell strengthens this hypothesis. While gCYA displays a more ubiquitous distribution and often incorporates in stress fibers, bCYA has a clear preference for protrusions [Hoock et al, 1991]. In microvascular peri- Fig.…”
Section: Introductionmentioning
confidence: 99%